Isogeometric analysis for geometric modelling and acoustic attenuation performances of reactive mufflers. (15th June 2020) - Xue, Yaqiang; Jin, Guoyong; Ye, Tiangui; Shi, Kangkang; Zhong, Saifeng; Yang, Chuanmeng
Abstract: In the present study, the acoustic attenuation performances of mufflers are predicted by employing three-dimensional isogeometric analysis (IGA) and multi-patch technique for the first time. Circular, elliptical and conical reactive expansion chamber mufflers are exactly parameterized by non-uniform rational B-splines (NURBS), and the Helmholtz equation governing the interior acoustic field is also solved by NURBS. Compared with traditional finite element method (FEM) which is rooted in Lagrange and Hermite functions, IGA can effectively avoid the time-consuming meshing and totally preserve exact geometrical information during the modelling-analysis process. The computational effectiveness of multi-patch IGA for calculating transmission loss is verified by comparing with experimental approach, boundary element method and other numerical methods from available research articles. The effects of geometry, such as shapes of the expansion cavity and lengths of the extended inlet/outlet are discussed in detail.